MENAKAR KONSEP TUNGKU TIGO SAJARANGAN-TALI TIGO SAPILIN DALAM MEMBANGUN KREATIVITAS GURU DI SEKOLAH DASAR - Arif, Fadli; Marta, Alfroki; Tulljanah, Rahmia; Apfani, Sry (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2024)
This research aims to examine the concept of Tungku Tigo Sajarangan-Tali Tigo Sapilin in building teacher creativity in elementary schools. The method used in this research is a qualitative method with a literature study approach. The results of this research show that the Tungku Tigo Sajarangan-Tali Tigo Sapilin concept is a leadership concept that applies in Minangkabau which consists of three actors, namely Niniak Mamak, Alim Ulama, and Cadiak Pandai. In building creativity among teachers in elementary schools, as a leader who sets an example, a school principal must continue to prioritize religious teachings in guiding teachers in elementary schools, and continue to remind his colleagues so that teacher creativity can be honed in a sustainable manner.